Experimental determination of the equivalent-layer shear stiffness of CLT through four-point bending of sandwich beams. (20th October 2018) - Perret, Olivier; Lebée, Arthur; Douthe, Cyril; Sab, Karam
Highlights: A new test is presented to measure the equivalent layer out-of plane shear stiffness of Cross Laminated Timber. The bending stiffness is directly measured from the rotation at support. Assumptions and validity of the model are verified numerically. The experimental study shows promising results with a reduced measurement dispersion. Abstract: In this paper, a new methodology for the experimental determination of the CLT equivalent cross-layer shear elastic modulus is suggested using a wooden core sandwich beam with Carbon Fiber Reinforced Polymer skins under four-point bending. The stiffness contrast between the wooden layer and the CFRP skins ensures that the bending stiffness of the sandwich beam is mostly driven by the CFRP skins and the shear force stiffness of the beam is mostly driven by the shear modulus of the wooden core. Several measurements for the determination of the bending stiffness of the sandwich beam are investigated. Particularly, it is shown that the suggested measurement of the bending stiffness from rotation at beam ends presents more reliable results than common measurements of curvature. Then the results of a preliminary experimental study are presented using this set-up and promising results are obtained: the equivalent cross-layer shear modulus is measured at 124 MPa which lies well within literature.